1997
DOI: 10.1063/1.474030
|View full text |Cite
|
Sign up to set email alerts
|

Transient hole-burning spectroscopy of associated ethanol molecules in the infrared: Structural dynamics and evidence for energy migration

Abstract: Transient spectral hole burning and hydrogen-bond breaking determined in different solutions of ethanol in deuterated ethanol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 26 publications
6
40
0
Order By: Relevance
“…[16][17][18] For this system it is also observed that the hydrogen bond is the main accepting mode in the relaxation of the O-H stretch vibration. The energy that is transferred from the O-H stretch vibration to the hydrogen bond causes the hydrogen bond to dissociate, and as a result a transient blueshifted absorption of dissociated ethanol cluster fragments is observed.…”
Section: ͑6͒mentioning
confidence: 91%
“…[16][17][18] For this system it is also observed that the hydrogen bond is the main accepting mode in the relaxation of the O-H stretch vibration. The energy that is transferred from the O-H stretch vibration to the hydrogen bond causes the hydrogen bond to dissociate, and as a result a transient blueshifted absorption of dissociated ethanol cluster fragments is observed.…”
Section: ͑6͒mentioning
confidence: 91%
“…[29][30][31][32][33]66 The main feature of the latter system is that vibrational relaxation of the excited OH (OD) stretching mode results in ultrafast breaking of the hydrogen bond at a time scale shorter than 2 ps. The broken hydrogen bond recovers at a time scale of ∼10 to 20 ps after which the temperature equilibration of the sample settles up.…”
Section: Pathways For Vibrational Energy Relaxationmentioning
confidence: 99%
“…As will be demonstrated below, when the d OD excited state relaxes, hydrogen bonds break [1,9,46], producing photoproduct g ODs. The resulting photoproduct g peak, located above the d band, is visible by T w ¼ 1:2 ps: The diagonal d band progressively contracts to the red as T w increases.…”
Section: Article In Pressmentioning
confidence: 97%
“…Comparison of the center of the preserved d band at T w ¼ 5:0 ps and the center of the initially excited d band (indicated by the horizontal line at 2490 cm À1 ) demonstrates that the preserved d band is contracted to the red and shifted off diagonal along the o m axis. For times longer than B5 ps, the peaks do not change shape significantly, but slowly decay in magnitude on a time scale of 10's of ps because of hydrogen bond recombination [1,9,46]. An important aspect of the 2D correlation spectrum is that the photoproduct g is spectrally separated in the plane from the equilibrium g band (see The T w dependence of the correlation spectra raises a number of questions.…”
Section: Article In Pressmentioning
confidence: 98%
See 1 more Smart Citation